Primus inter pares effect in high schools - Dizdarević, Denis; Leskovar, Robert; Vukovič, Goran (Frontiers in Psychology, 2024)
Primus inter pares effect or better-than-average effect is cognitive bias known as illusory superiority in which individuals overestimate their positive abilities and traits in comparison to others. Overestimation and bias are often accompanied with various dangers on a personal, organizational or even societal level. We investigated the presence of overestimation among high school graduates in Slovenia in areas of teamwork, interpersonal skills, emotional intelligence, problem solving, and decision making. Although overestimation was present in all areas, results have also shown indications of indecisiveness. Overestimation was highest in the area of interpersonal skills, which is more of a social skill area in comparison with decision making or problem solving. Individuals probably receive more feedback over the course of high school in decision making, problem solving, and teamwork than in interpersonal skills, as those can directly impact grades while interpersonal skills less so.